Mature Teratoma of The Lung : A Case Report - Priangga Adi Wiratama; Alphania Rahniayu; Vira Yasmina Ramadhani (Universitas Muhammadiyah Semarang, 2023)
Background: Mature teratoma is a germinal cell tumor that is commonly found in ovaries and testis. Mature teratoma in the lung region is a rare case. According to the literature there are only 67 cases worldwide starting from 1939 to 2007. There were one cases in Dr. Soetomo general hospital during January 2013 – December 2017.Objective: Mature teratoma in the lung region is a rare case. Presenting in a case report would be beneficial for pathology databaseCase Presentation: A 19 years old man came to hospital with shortness of breath within 3 months ago. It was followed with hemoptysis, trichoptysis and coughing out tooth. CT Scan examination showed an irregular walled cavity with semisolid component and calcification along with a description of